2019
DOI: 10.1002/hed.26069
|View full text |Cite
|
Sign up to set email alerts
|

The role of a post therapeutic surveillance program for sinonasal malignancies: Analysis of 417 patients

Abstract: Background: Post therapeutic surveillance of head and neck neoplasms is a still debated issue in the current literature: although different works tried to establish frequency, modality, and efficacy of a routine follow-up, little evidence has been produced, in particular considering only sinonasal malignancies.Methods: A retrospective review of patients treated for sinonasal malignancies in a single tertiary center and followed through a regular program of follow-up was carried out. Rate of recurrence, locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 32 publications
1
49
0
Order By: Relevance
“…Initial radiological staging of sinonasal tumors requires detailed information on local tumor extent, especially with regard to infiltration of the orbit and skull base. As represented in the AJCC cancer staging system, this information determines the T category and serves as a strong predictor of the 5‐year disease‐specific survival 30‐33 . However, despite state‐of‐the‐art high‐resolution cross‐sectional imaging, radiological assessment needs to be complemented by exploration of the tumor under general anesthesia, in order to ultimately assess local respectability‐defining factors 1,15,28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial radiological staging of sinonasal tumors requires detailed information on local tumor extent, especially with regard to infiltration of the orbit and skull base. As represented in the AJCC cancer staging system, this information determines the T category and serves as a strong predictor of the 5‐year disease‐specific survival 30‐33 . However, despite state‐of‐the‐art high‐resolution cross‐sectional imaging, radiological assessment needs to be complemented by exploration of the tumor under general anesthesia, in order to ultimately assess local respectability‐defining factors 1,15,28 .…”
Section: Discussionmentioning
confidence: 99%
“…As represented in the AJCC cancer staging system, this information determines the T category and serves as a strong predictor of the 5-year diseasespecific survival. [30][31][32][33] However, despite state-of-the-art high-resolution cross-sectional imaging, radiological assessment needs to be complemented by exploration of the tumor under general anesthesia, in order to ultimately assess local respectability-defining factors. 1,15,28 While superiority of FDG-PET/CT over single-modality PET, CT and MRI imaging was previously shown for the initial staging of head and neck cancer in general, 34,35 only a few studies have investigated the diagnostic accuracy of hybrid PET imaging specifically for the initial staging of sinonasal tumors.…”
Section: Main Findingsmentioning
confidence: 99%
“…This is in accordance with previously published data showing that the majority of recurrences in sinonasal malignancies are local (ranging between 27%-56%) and represent the leading cause of disease specific mortality. [7][8][9][10][11][12][13] Furthermore, we noted that tumor histology was associated with recurrence rates and recurrence pattern. The highest recurrence rate (70%) was observed in patients with mucosal melanoma, followed by esthesioneuroblastoma (44%) and SCC (25%).…”
Section: Discussionmentioning
confidence: 73%
“…In a meta-analysis of 26 studies including 390 patients with esthesioneuroblastoma, local recurrence was observed in 29% of the patients and regional recurrence in 16%. [7][8][9][10][11][12][13][14][15] A subgroup analysis of SCC patients (being nearly half of our patient cohort) demonstrated that the majority of patients had advanced disease and were treated with primary surgery and adjuvant radiation. Recurrence was noted in 26.5% of patients, was mainly local and was diagnosed by nasal endoscopy during the first two years of follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up. Postoperative management and follow-up for patients undergoing sinus and skull base procedures followed standardized protocols already established at our Department [7][8][9]. Nasal packing are removed on the second postoperative day and following endonasal medications are performed as needed, until hospital discharge.…”
Section: Patients Management During Covid-19 Two-months Periodmentioning
confidence: 99%